(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
STEM (Science, Technology, Engineering, and Mathematics) anxiety is an important emotional barrier that affect students’ engagement, academic performance, and continuation in STEM education. This paper presents a systematic review of empirical studies on STEM anxiety, focusing on gender differences, socio-economic factors, geographic and cultural variation, and medium of instruction. Peer-reviewed research published between January 2000 and December 2018 was reviewed using a structured methodology. The findings show that gender differences are common, with female students generally reporting higher levels of anxiety, although these differences vary across contexts and countries. Cross-national studies indicate the presence of a gender-equality paradox in economically developed societies. Socio-economic influences affect STEM anxiety through family background and educational environment, while geographic variation highlights the role of cultural norms and assessment practices. Despite its importance, the role of the medium of instruction has received limited research attention. The paper concludes by outlining implications for educational practice, policy, and future research.